Granulocyte‐colony stimulating factor‐producing uterine cervical cancer treated with chemoradiotherapy: A case report with mutation analysis and literature review. Issue 1 (6th November 2020) - Shiba, Shintaro; Oike, Takahiro; Ando, Ken; Yoshimoto, Yuya; Takayama, Yoshiyasu; Ohno, Tatsuya
Abstract: Granulocyte‐colony stimulating factor‐producing uterine cervical cancer is a rare aggressive disease, which may be genetically distinct from other uterine cervical cancers. Abstract : Granulocyte‐colony stimulating factor‐producing uterine cervical cancer is a rare aggressive disease, which may be genetically distinct from other uterine cervical cancers.